2005
DOI: 10.1097/01.ju.0000150425.09317.67
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus Calmette-Guerin Versus Epirubicin for Primary, Secondary or Concurrent Carcinoma in Situ of the Bladder: Results of a European Organization for the Research and Treatment of Cancer—genito-Urinary Group Phase Iii Trial (30906)

Abstract: No significant difference in CR rates could be demonstrated with intravesical instillations of epirubicin or BCG. Time to recurrence was significantly longer in patients treated with BCG after having achieved a CR. More CIS recurrences were found in patients treated with epirubicin. For time to progression and survival longer followup is warranted. Side effects were more frequent in patients on BCG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(40 citation statements)
references
References 19 publications
0
35
0
3
Order By: Relevance
“…In the meta-analysis, the different progression rate between papillary tumours and Cis tumours is emphasized, which was reported to be, respectively, 6.4 and 13.9% and the importance is stressed of maintenance therapy to obtain advantages in the progression rate [6]. In an EORTC phase III trial (number 30906), 168 patients were randomised to receive BCG (84) or epirubicin (84) and the overall CR rate was 56% for epirubicin and 65% for BCG, time to bladder tumour recurrence, after CR, was longer in patients treated with BCG vs those receiving epirubicin [16]. Bohle et al [17] reported, in a metaanalysis of 2,410 patients, the better results with maintenance BCG versus mitomycin C as far as concerns progression rate.…”
Section: Discussionmentioning
confidence: 99%
“…In the meta-analysis, the different progression rate between papillary tumours and Cis tumours is emphasized, which was reported to be, respectively, 6.4 and 13.9% and the importance is stressed of maintenance therapy to obtain advantages in the progression rate [6]. In an EORTC phase III trial (number 30906), 168 patients were randomised to receive BCG (84) or epirubicin (84) and the overall CR rate was 56% for epirubicin and 65% for BCG, time to bladder tumour recurrence, after CR, was longer in patients treated with BCG vs those receiving epirubicin [16]. Bohle et al [17] reported, in a metaanalysis of 2,410 patients, the better results with maintenance BCG versus mitomycin C as far as concerns progression rate.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29] Evidence on treatment of patients who relapse following BCG treatment is very limited. However, data have demonstrated adverse cancer-specific survival among patients with NMIBC recurrence after BCG who undergo delayed versus early cystectomy.…”
Section: Bcg Relapse and Salvage Regimensmentioning
confidence: 99%
“…Between 20 and 40% of NMIBC patients, depending on FU time and risk profile, have a recurrence after adequate BCG therapy [75,80,85]. When BCG is used as therapy, it induces a 70% initial complete response rate, which remains so in 50% after long FU.…”
Section: Bcg Failurementioning
confidence: 98%
“…Fewer than 5% of patients never complete the induction course, meaning they never had sufficient BCG therapy [80,85]. In BCG-intolerant patients, certainly in those who never completed the induction course, intravesical therapy with another drug at the time of recurrence is worth trying [86].…”
Section: Bcg Failurementioning
confidence: 99%